Stratigraphic constraints on the Lower Cretaceous Orallo Formation, southeastern Queensland: U–Pb dating of bentonite and palynostratigraphy of associated strata. Issue 3 (3rd April 2021) - Cooling, J. J.; Crowley, J. L.; McKellar, J. L.; Esterle, J. S.; Nicoll, R. S.; Bianchi, V.
Abstract: This study presents two chemical abrasion-thermal ionisation mass spectrometry (CA-TIMS) U–Pb zircon ages from tuffs as well as palynostratigraphic results from the embracing sedimentary succession of the Orallo Formation, Surat Basin, Queensland. Samples were taken from two Geological Survey of Queensland (GSQ) stratigraphic holes, GSQ DRD 26 and GSQ Roma 2. Palynological results assign the upper part of the Orallo Formation to the lower part of the Ruffordiaspora australiensis Interval Zone rather than the upper part of this zone as previously indicated. A late Valanginian isotopic date of 134.38  ±  0.04 Ma from GSQ DRD 26 and an early Hauterivian date of ≤132.46  ±  0.36 Ma from GSQ Roma 2 give the Orallo Formation a Berriasian?/Valanginian–Hautevarian age, rather than the previously inferred Berriasian–Valanginian age determined without any geochronological control. Additionally, when combined with previously published geochronological dates from the Westbourne Formation, these ages suggest that, in the Surat Basin succession, the Jurassic–Cretaceous boundary most likely lies within the Gubberamunda Sandstone. KEY POINTS: Two U–Pb CA-TIMS ages of 134.38 ± 0.04 Ma and ≤132.46 ± 0.36 Ma have been found, based on zircons extracted Orallo Formation tuffs. Sediments surrounding the two tuffs the zircons were extracted from yielded palynofloras assignable to the lower part of the Ruffordiaspora australiensis Interval Zone. These dates, combined with earlier work, show the Orallo Formation to be of Berriasian?/Valanginian–Hautevarian age.